The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acsabm.1c00628
|View full text |Cite
|
Sign up to set email alerts
|

Porous Oxyhydroxide Derived from Metal–Organic Frameworks as Efficient Triphosphatase-like Nanozyme for Chromium(III) Ion Colorimetric Sensing

Abstract: The dephosphorylation that involves the removal of a phosphate group from a substrate molecule plays a significant role in living organisms. An enzyme mimic (nanozyme) with phosphatase-like catalytic activity has recently received attention in terms of its capacity for dephosphorylation. In this study, three types of highly porous oxyhydroxide with remarkable triphosphatase-like catalytic activities, ZrOOH, GdOOH, and HfOOH, have been prepared through the transformation of metal−organic frameworks (MOFs) using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…As mentioned above, the UIO-66 precursor has no phosphatase-like activity and only can hydrolyze the phosphate group after being treated with an alkaline solution to generate ZrO X -OH. The reason may be that the rich −OH on the surface of ZrO X -OH as a nucleophilic agent attacked the electropositive phosphorus atom, leading to the cleavage of the P–O bonds. , Therefore, it can be deduced that −OH on the surface of ZrO X -OH plays a very important role in phosphatase-like activity. To evaluate the relationship between −OH on the surface of ZrO X -OH and phosphatase-like activity, we explored the effects of pH and organic acids on the activity of ZrO X -OH nanozymes.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, the UIO-66 precursor has no phosphatase-like activity and only can hydrolyze the phosphate group after being treated with an alkaline solution to generate ZrO X -OH. The reason may be that the rich −OH on the surface of ZrO X -OH as a nucleophilic agent attacked the electropositive phosphorus atom, leading to the cleavage of the P–O bonds. , Therefore, it can be deduced that −OH on the surface of ZrO X -OH plays a very important role in phosphatase-like activity. To evaluate the relationship between −OH on the surface of ZrO X -OH and phosphatase-like activity, we explored the effects of pH and organic acids on the activity of ZrO X -OH nanozymes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the bubble–liquid–particle triphase interface region promotes the generation of ROS to trigger the surface hydroxylation of the CMNC nanoparticles. Our previous work confirmed that the surface hydroxyl groups present in phosphatase-mimicking nanozymes play an extremely important role in ensuring a phosphatase-like activity. In the current system, we therefore assumed that the abundance of surface hydroxyl groups on the CMNC nanoparticles could serve as nucleophilic agents to directly attack the electropositive phosphorus atoms of the phosphoester substrates and enhance the catalytic dephosphorylation activity.…”
Section: Resultsmentioning
confidence: 99%
“…22 Recently, some nanomaterial-based phosphatase mimics to facilitate the hydrolysis of phosphate esters have emerged for ion analysis. 31,66,70 For instance, Song et al demonstrated that single-atom Ce-N-C has good phosphatase activity, 70 which could catalyze the dephosphorylation of organophosphates. Simultaneously, they discovered that Al 3+ could specifically attach to the O atom in the nanozyme, inhibiting its phosphatase-like activity.…”
Section: Expansion Of Enzyme-like Activity Typesmentioning
confidence: 99%
“…On the other hand, H 2 O 2 is a redox agent, and the use of high-concentration H 2 O 2 may change the form of analytes in original samples. Instead, a few studies have explored the use of oxidases, 64,65 oxidoreductases, 21,22 phosphatase mimics 31,66 or multiactivity nanozymes 24,67,68 for toxic ion detection. For instance, using ascorbic acid-coated platinum nanoparticles (AA-PtNPs) with catalase properties to catalyze the decomposition of H 2 O 2 to produce hydrogen gas, the produced gas can expel water from the device, leading to a reduction in the weight of the device, 69 and because Ag + can inhibit the AA-PtNPs' catalytic activity and reduce gas production, it is possible to measure the Ag + content by observing changes in the device's weight (Fig.…”
Section: Expansion Of Enzyme-like Activity Typesmentioning
confidence: 99%